PEMANTAUAN PERUBAHAN PERILAKU CTPS PADA IBU DAN BALITA DI DESA PUNDONG II KABUPATEN SLEMAN - Kenanga Sukmaningrum; Tasya Nurul Amaliah; Fafa Nur Azila; Munifah Munifah; Isnani Qodriyani; Tuntas Bagyono; Yamtana Yamtana (JPS : Jurnal Pengabdian Serulingmas, 2022)
Bad hand washing habits can increase the emergence of bacteria that enter the body. Hand washing with soap (CTPS) in running water is a way to reduce the number of pathogenic germs on hands. The habit of mothers and toddlers washing their hands before feeding or after defecating can reduce the risk of toddlers getting stunted. Pundong II Village is known to have 3 (three) toddlers who still weigh less than the standard weight for their age, 1 (one) of the 3 (three) toddlers is malnourished. The purpose of this study was to monitor handwashing with soap (CTPS) on mothers and toddlers. The research method used is descriptive. The results obtained are mothers and toddlers successfully carry out handwashing with soap (CTPS) correctly, after monitoring 3 times. This service has the impact of mothers and toddlers knowing how to properly wash their hands with soap (CTPS) in order to reduce the risk of stunting in toddlers.